Sliding mode control of buildings with base-isolation hybrid protective system. - Zhao, Bin (Earthquake engineering & structural dynamics.)
This paper investigates the application of the sliding mode control (SMC) strategies for reducing the dynamic responses of the building structures with base isolation hybrid protective system. It focuses on the use of reaching law method, a most attractive controller design approach of the SMC theory, for the development of control algorithms. By using the constant plus proportional rate reaching law and the power rate reaching law, two kinds of hybrid control methods are presented. The compound equation of motion of the base isolated hybrid building structures, which is suitable for numerical analysis, has been constructed. The simulation results are obtained for an eight storey shear building equipped with base isolation hybrid protective system under seismic excitations. It is observed that both the constant plus proportional rate reaching law and the power rate reaching law hybrid control method presented in this paper are quite effective.